Analisis Rantai Pasok Berkelanjutan Limbah Kayu Furnitur Sebagai Pendukung Ketahanan Ekonomi Lokal - Haryudiniarti, Ayu Nurul; Restuasih, Sinta; Faizah, Safira (TECHNO-SOCIO EKONOMIKA, 2025)
Wood waste constitutes a significant component of solid waste, attributable to the rising demand for household and office furniture. A viable solution to mitigate this issue entails the recycling of wood waste into charcoal briquettes through the implementation of a sustainable supply chain method. This recycling process is anticipated to generate added value for furniture craftsmen, particularly in terms of economic enhancement. The first step in this research is to conduct interviews with furniture craftsmen to ascertain the volume of wood waste generated on a daily, weekly, or monthly basis, as well as the selling price of the wood waste. Next, the recycling process of wood waste into briquette charcoal is carried out to determine the amount of briquette charcoal produced. The results of the process demonstrate that converting wood waste into briquetted charcoal can significantly increase the added value, thereby providing economic benefits for furniture craftsmen. From economic calculations, briquetted charcoal that undergoes a recycling process and additional ingredients has an estimated selling value of four times that of wood waste that is not processed or sold directly to other parties.